2012
DOI: 10.1364/oe.20.00a418
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic-photonic arrays with aperiodic spiral order for ultra-thin film solar cells

Abstract: We report on the design, fabrication and measurement of ultra-thin film Silicon On Insulator (SOI) Schottky photo-detector cells with nanostructured plasmonic arrays, demonstrating broadband enhanced photocurrent generation using aperiodic golden angle spiral geometry. Both golden angle spiral and periodic arrays of various center-to-center particle spacing were investigated to optimize the photocurrent enhancement. The primary photocurrent enhancement region is designed for the spectral range 600nm-950nm, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…The history of mathematical phyllotaxis started in the first half of the nineteenth century when the brothers Auguste and Louis Bravais presented the first quantitative treatment of the phenomenon and recognized the relevance of the theory of continued fractions in this area (i.e., in the so-called cylindrical representation of phyllotaxis) [70]. Aperiodic Vogel spiral arrays of nanoparticles are rapidly emerging as a powerful nanophotonics platform with distinctive optical properties of interest to a number of engineering applications [42,58,[71][72][73][74][75][76][77][78]. This fascinating category of deterministic aperiodic media features circularly symmetric scattering rings in Fourier space entirely controlled by simple generation rules that induce a very rich structural complexity.…”
Section: Structural Properties Of Aperiodic Arraysmentioning
confidence: 99%
See 2 more Smart Citations
“…The history of mathematical phyllotaxis started in the first half of the nineteenth century when the brothers Auguste and Louis Bravais presented the first quantitative treatment of the phenomenon and recognized the relevance of the theory of continued fractions in this area (i.e., in the so-called cylindrical representation of phyllotaxis) [70]. Aperiodic Vogel spiral arrays of nanoparticles are rapidly emerging as a powerful nanophotonics platform with distinctive optical properties of interest to a number of engineering applications [42,58,[71][72][73][74][75][76][77][78]. This fascinating category of deterministic aperiodic media features circularly symmetric scattering rings in Fourier space entirely controlled by simple generation rules that induce a very rich structural complexity.…”
Section: Structural Properties Of Aperiodic Arraysmentioning
confidence: 99%
“…Moreover, it has been recently demonstrated that Vogel spiral arrays of metallic nanoparticles feature distinctive structural resonances and produce polarization insensitive, planar light diffraction across a broad spectral range, referred to as circular light scattering [72]. The planar diffraction property of Vogel spirals is ideally suited to enhance light-matter interactions on planar substrates and recently led to the demonstration of thin-film solar cell absorption enhancement, light emission, and second harmonic generation enhancement using metal-dielectric arrays [42,77,78]. Another fascinating feature of Vogel spiral diffracting elements is their ability to support distinctive scattering resonances encoding well-defined numerical sequences in the orbital angular momentum (OAM) of light [72][73][74][75], potentially leading to novel applications to singular optics and optical cryptography [79].…”
Section: Structural Properties Of Aperiodic Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to find out the best structures ,a large number of research has been done, including the front gratings [2]、the back gratings [3]、the dual-gratings [4]、 and the photonic crystal. Besides, many researches focus on the arrangement of the particles ,including Gaussian disorder surface [5] and gold angle arrangement surface [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, however, alternative lighttrapping schemes have been proposed based on aperiodic photonic patterns. Among these proposals, several have investigated structures with complete aperiodicity [3][4][5][6] of either random 3,4,6 or deterministic 5 nature. Such structures were found to improve solar absorption, with the additional benefit of performance insensitivity to incidence angle and polarization.…”
mentioning
confidence: 99%